a high indices theorem without a nontrivial solution - Johansson, Bo I. (Mathematica Scandinavica, 2010)
In this paper we will extend the high indices Theorem by Hardy-Littlewood, which says that an Abel summable series, where the exponents fulfil a Hadamard gap criterion, is convergent and it converges to its Abel sum. The focus here is concerning a class of summability methods and their critical rate of convergence, i.e. for a given summability method what is its rate of convergence implying that the series must be identically constant.